Effect of Calcination Temperature on Structural, Morphological and Optical Properties of Copper Oxide Nanostructures Derived from Garcinia mangostana L. Leaf Extract - Yu Bin Chan; Vidhya Selvanathan; Lai-Hock Tey; Md. Akhtaruzzaman; Farah Hannan Anur; Sinouvassane Djearamane; Akira Watanabe; Mohammod Aminuzzaman (Nanomaterials, 2022)
Synthesis of copper oxide (CuO) nanostructures via biological approach has gained attention to reduce the harmful effects of chemical synthesis. The CuO nanostructures were synthesized through a green approach using the Garcinia mangostana L. leaf extract and copper (II) nitrate trihydrate as a precursor at varying calcination temperatures (200–600 °C). The effect of calcination temperatures on the structural, morphological and optical properties of CuO nanostructures was studied. The red shifting of the green-synthesized CuO nanoparticles’ absorption peak was observed in UV-visible spectrum, and the optical energy bandgap was found to decrease from 3.41 eV to 3.19 eV as the calcination temperatures increased. The PL analysis shown that synthesized CuO NPs calcinated at 500 °C has the maximum charge carriers separation. A peak located at 504–536 cm−1 was shown in FTIR spectrum that indicated the presence of a copper-oxygen vibration band and become sharper and more intense when increasing the calcination temperature. The XRD studies revealed that the CuO nanoparticles’ crystalline size was found to increase from 12.78 nm to 28.17 nm, and dislocation density decreased from 61.26 × 1014 cm−1 to 12.60 × 1014 cm−1, while micro strain decreased from 3.40 × 10−4 to 1.26 × 10–4. From the XPS measurement, only CuO single phase without impurities was detected for the green-mediated NPs calcinated at 500 °C. The morphologies of CuO nanostructures were examined using FESEM and became more spherical in shape at elevated calcination temperature. More or less spherical nanostructure of green-mediated CuO calcinated at 500 °C were also observed using TEM. The purity of the green-synthesized CuO nanoparticles was evaluated by EDX analysis, and results showed that increasing calcination temperature increases the purity of CuO nanoparticles.